Radiotherapy for stage IVa thymoma—Shanghai Chest experience - Wang, Changlu; Gao, Lanting; Fang, Wentao (Mediastinum; Vol 3 (March 2019): Mediastinum, 2019)
To investigate the effect of two modalities, radiotherapy (RT) and surgery plus entire hemithoracic radiotherapy (EHRT), on stage IVa thymoma. Patients enrolled in this study meet the following criteria: histologically proven thymoma; primary stage IVa or pleural dissemination after initial curative treatment. One treatment modality is intensity-modulated radiotherapy (IMRT) for pleural lesions with a dose ranging from 30–50 Gy, the other is macroscopically surgical resection plus EHRT with a dose of 13 Gy in 13 fractions. From July 2012 to April 2018, there were totally 56 patients enrolled in this study. The median age was 45 years old (range, 20–75 years old). There were 35 male and 21 female patients. The histology subtype distribution was 1 AB, 8 B1, 20 B2 and 27 B3, respectively. Thirty-one patients received IMRT for pleural dissemination and the response rate (CR + PR) was 97%. The mean local control time was 40 months (95% CI, 32.6–47.3 months). The in-field and out-field recurrence were 32% and 94%, respectively. The 2-year progression free survival (PFS) was 18%. While for patients who were treated by surgery plus EHRT, the in- and out-field recurrence were 8% and 16%, respectively. The 2-year PFS was 40%. The 2-year PFS for B1, B2 and B3 were 20%, 50% and 23%, respectively (P=0.255). Major toxicity occurred in IMRT group, 5 died of radiation-induced pneumonitis. Both IMRT and surgery plus EHRT showed good local control for stage IVa thymoma. Since stage IVa thymoma has a tendency to involve the whole hemithorax, surgery plus EHRT has a potential to produce longer PFS.